Random Fixed Point of Random Hardy-Roger Almost Contraction for Solving Nonlinear Stochastic Integral Equations: Plern Saipara, Dhananjay Gopal, Wiyada Kumam - Team, Support (Thai Journal of Mathematics, 2018)
The objective of this article is to prove a new random fixed point theorem for a random Hardy-Roger almost contraction mapping. The main result in this article is the identification of some random fixed point theorems and the interrelated applications. This result is convenient to determine the existence of solution of a stochastic nonlinear integral equation in a Banach space.